Interview of Paul Robert Streich by Brian Shoemaker - Streich, Paul Robert (Byrd Polar Research Center Archival Program, 2005)
Admiral Richard E. Byrd, pp. 16-17, 25-26, 30, 37, 57, 70, 74 Gus Shinn, pp. 17, 69 Trigger Hawks, pp. 17 Gordon Hebbe, pp. 18, 29, 30 Toni Hebbe, pp. 18 Richard Byrd Jr., pp. 26 Colonel Roscoe, pp. 26 Paul Siple, pp. 26, 34, 75 Dick Black, pp. 29 Walter Sullivan, pp. 33 Lloyd Beebe, pp. 33 Admiral Dufek, pp. 34, 40, 45, 57, 69 Eddie Goodale, pp. 34-35 Jack Bursey, pp. 34, 42 Herb Whitney, pp. 37 Bob Graham, pp. 41 Glen Lathrop, pp. 47, 50, 56, 69 Don Sullivan, pp. 53 Dan Slovinsky, pp. 54 Chief Moss, pp. 55 John Cameron Swayze, pp 56 Max Kiel, pp. 56 Wes See, pp. 60 Dick Young, pp. 68 Dan Slovinsky, pp. 71 Dick Swegner, pp. 71 Hary Speed, pp. 72 Bud Weddick, pp. 75 Eddie Goodale, pp. 75 The media can be accessed at the links below. Audio Part 1: http://streaming.osu.edu/knowledgebank/byrd/oral_history/Bob_Streich_1.mp3 Audio Part 2: http://streaming.osu.edu/knowledgebank/byrd/oral_history/Bob_Streich_2.mp3 Commander Streich was an aviator in 1955 during the International Geophysical Year build-up in Antarctica. After summarizing his experiences in high school (Casper, Wyoming) he goes on to discuss his enlistment in the Navy Z-5 program. After receiving his wings, he was assigned to the Heavy Photographic Squadron. The squadron mapped Newfoundland and Labrador over the course of one summer. Streich was later involved in intelligence photography for AIRLANT. After assignments in Europe and Africa he had a long assignment in the Alaska CDR. Streich volunteered for Operation Deepfreeze in 1955. The preparations for the trip, the trip itself, and the arrival at Little America are described. Streich discusses his impressions of Admiral Byrd and describes the development of the first runway on ice at McMurdo Station, the construction of which was headed by Byrd and Hebbe. He also describes winter conditions, moving sea ice, and the flying reconnaissance used to locate the trail from Little America to Byrd Station. Streich discusses the challenges to survival after his plane crashed in a whiteout, after which ...